Assessing children's relationships with pet dogs: A multi‐method approach. Issue 1 (20th June 2022) - Kerns, Kathryn A.; Dulmen, Manfred H. M.; Kochendorfer, Logan B.; Obeldobel, Carli A.; Gastelle, Marissa; Horowitz, Alexandra
Abstract: Relationships with pet dogs are thought to provide substantial benefits for children, but the study of these relationships has been hindered by a lack of validated measures. Approaches to assessing the quality of children's pet dog relationships have tended to focus on positive relationship qualities and to rely on self‐report questionnaires. The aim of this study was to develop and test multiple measures that could be used to assess both positive and negative features of children's relationships with pet dogs. In a sample of 115 children ages 9–14 years who were pet dog owners, we assessed six qualities of pet dog relationships: Affection, Nurturance of Pet, Emotional Support from Pet, Companionship, Friction with Pet, and Pets as Substitutes for People. All qualities were assessed with child questionnaires, parent questionnaires, and child daily reports of interactions with pets. We found substantial convergence in reports from different observers and across different measurement approaches. Principal components analyses and correlations suggested overlap for many of the positive qualities, which tended to be distinct from negative relationship qualities. The study provides new tools which could be used to test further how relationships with pets contribute to children's development.